Levator Ani Avulsion as the Key Mediator Between Vaginal Delivery and Pelvic Organ Prolapse: A Systematic Review and Meta-Analysis of Imaging Studies - Heristanto; Rahajeng (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Vaginal childbirth is universally recognized as the primary etiological factor for pelvic organ prolapse (POP), yet the precise biomechanical cascade remains a subject of intense investigation. While connective tissue attenuation contributes to support failure, recent advanced imaging evidence suggests that levator ani avulsion (LAA)—a macroscopic traumatic detachment of the puborectalis muscle from the pubic ramus—acts as the fundamental structural mediator. This study aimed to systematically review and meta-analyze imaging-based literature to quantify the mediating role of LAA in the pathogenesis of POP. Methods: We conducted a systematic review and meta-analysis of observational studies utilizing magnetic resonance imaging (MRI) and 3D/4D Transperineal Ultrasound. The search strategy targeted longitudinal and cross-sectional studies comparing women with confirmed LAA to those with intact pelvic floors following vaginal delivery. Data were extracted regarding the prevalence of avulsion, pelvic organ prolapse quantification (POP-Q) stages, and levator hiatus dimensions. The primary outcome was the Odds Ratio (OR) of significant POP (Stage ³2). Secondary outcomes included quantitative analysis of hiatal ballooning. Data were synthesized using a random-effects model. Results: The analysis included 3,218 women across 9 high-quality imaging studies. The pooled analysis revealed a profound and statistically significant association between LAA and POP, with a pooled Odds Ratio of 3.84 (95% CI: 2.65–5.56; p < 0.0001). Women with LAA demonstrated a significantly larger levator hiatal area on Valsalva compared to those with intact muscles (Mean Difference: +6.03 cm²), confirming that avulsion leads to intractable hiatal ballooning. Long-term follow-up data (up to 23 years) indicated that this muscular defect does not heal and is associated with a progressive deterioration in pelvic organ support over time. Conclusion: Levator ani avulsion is the critical biomechanical mediator converting the event of vaginal delivery into the chronic pathology of prolapse. The injury compromises the dynamic closure of the levator hiatus, resulting in hiatal ballooning and subsequent apical and anterior compartment descent. These findings necessitate a paradigm shift in obstetric counseling and emphasize the need for preventative strategies to minimize traumatic muscle injury during the second stage of labor.